1999
DOI: 10.1161/01.atv.19.7.1796
|View full text |Cite
|
Sign up to set email alerts
|

Storage of Tissue-Type Plasminogen Activator in Weibel-Palade Bodies of Human Endothelial Cells

Abstract: Abstract-Tissue-type plasminogen activator (t-PA) is acutely released by endothelial cells. Although its endothelial storage compartment is still not well defined, t-PA release is often accompanied by release of von Willebrand factor (vWf), a protein stored in Weibel-Palade bodies. We investigated, therefore, whether t-PA is stored in these secretory organelles. Under basal culture conditions, a minority of human umbilical vein endothelial cells (HUVEC) exhibited immunofluorescent staining for t-PA, which was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 42 publications
2
44
0
Order By: Relevance
“…32,52 Weibel-Palade bodies also contain premature von Willebrand factor, interleukin-8, endothelin-1, ␣1,3 fucosyltransferase, CD63, 53,54 and possibly tissue plasminogen activator (t-PA). 40,55 Our findings raise the question of whether the other contents of WPBs also display differential signaling. Endothelial t-PA is released in response to cAMP-raising agents, suggesting that t-PA secretion more closely resembles VWF than P-selectin.…”
Section: Differential Par and Camp-dependent Exocytosis 2741mentioning
confidence: 80%
See 1 more Smart Citation
“…32,52 Weibel-Palade bodies also contain premature von Willebrand factor, interleukin-8, endothelin-1, ␣1,3 fucosyltransferase, CD63, 53,54 and possibly tissue plasminogen activator (t-PA). 40,55 Our findings raise the question of whether the other contents of WPBs also display differential signaling. Endothelial t-PA is released in response to cAMP-raising agents, suggesting that t-PA secretion more closely resembles VWF than P-selectin.…”
Section: Differential Par and Camp-dependent Exocytosis 2741mentioning
confidence: 80%
“…38 However, this observation is controversial because other studies have shown that t-PA is stored in WPBs in HUVECs. [39][40][41] Indeed, some of the observed differences in localization of t-PA have been ascribed to subtle differences in tissue culture methods. 39 Accordingly, we examined the localization of VWF and P-selectin in our cell-culture system by performing immunostaining and confocal microscopy.…”
Section: Selective Release Of Weibel-palade Bodies That Contain Predomentioning
confidence: 99%
“…By constitutive secretion, the newly synthesised protein continuously leaves the Golgi compartment in transport vesicles that fuse with the cell membrane. By regulated secretion, on the other hand, t-PA is released from small dense vesicles and/or the Weibel-Palade bodies [38][39][40]. The intracellular storage pool of t-PA is quite large, and it follows that the regulated pathway allows local intravascular t-PA concentrations to increase rapidly and substantially [41,42].…”
Section: Regulation Of Intravascular Fibrinolysis In Vivomentioning
confidence: 99%
“…The studies were also carried out to discover the mechanism responsible for the release of t-PA. They confirmed its release from endothelial cell and additionally indicated Weibel-Pallade bodies as the site of t-PA reservoirs (similarly to vWF) [14,15].…”
Section: Influence Of Ufh Vs Lmwhs On Haemostatic Factors In Huvec Cumentioning
confidence: 66%